A Trickster in Disguise: Hyaluronan’s Ambivalent Roles in the Matrix - Bohaumilitzky, Lena; Huber, Ann-Kathrin; Stork, Eva Maria; Wengert, Simon; Woelfl, Franziska; Boehm, Heike (Frontiers in Oncology, 2017)
Hyaluronan (HA) is a simple but diverse glycosaminoglycan. It plays a major role in aging, cellular senescence, cancer and tissue homeostasis. In which way HA affects the surrounding tissues depends on the molecular weight of HA. Whereas high molecular weight HA is associated with homeostasis and protective effects, HA fragments tend to be linked to the pathologic state. Furthermore, the interaction of HA with its binding partners, the hyaladherins, like CD44, is essential for sustaining tissue integrity and is likewise related to cancer. The naked mole rat, a rodent species, possesses a special form of very high molecular weight HA, which is associated to the extraordinary cancer resistance and longevity of those animals. This review addresses HA and its diverse facets: from HA synthesis to degradation, from oligomeric HA to very high molecular weight HA and from its beneficial properties to the involvement in pathologies. We further discuss the functions of HA in the naked mole rat and compare them to human conditions. Though intensively researched, this simple polymer bears some secrets that may hold the key for a better understanding of cellular processes and the development of diseases, such as cancer.